PENGARUH JOB INVOLVEMENT DAN JOB CHARACTERISTICS TERHADAP JOB OUTCOME MELALUI WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT XYZ [THE EFFECT OF JOB INVOLVEMENT AND JOB CHARACTERISTICS ON JOB OUTCOMES THROUGH WORK ENGAGEMENT AS A MEDIATING VARIABLE IN PT XYZ EMPLOYEES] - Yeninda Yaumil Anam; Daniel Ong (Feedforward: Journal of Human Resource, 2024)
The purpose of this research is to determine the effect of 1) Job Involvement on Job Outcome; 2) Job Involvement towards Work Engagement; 3) Job Characteristics on Job Outcomes; 4) Job Characteristics on Work Engagement; 5) Work Engagement towards Job Outcomes; 6) Work Engagement as a mediating variable between Job Involvement and Job Outcome; and 7) Work Engagement as a mediating variable between Job Characteristics and Job Outcomes. The respondents to this research are employees who work at PT. XYZ. The method used in this research is a quantitative method, using data collection in the form of an online questionnaire. The data collection technique in this research uses a non-probability sampling technique with a convenience sampling method, where the respondents are only employees who work at PT. XYZ. The number of samples used in this research was 200 respondents. Statistical data analysis in this research uses Structural Equation Modeling where data processing uses the SmartPLS 3.2.9 application. The results obtained from this research are 1) Job Involvement has a positive effect on Job Outcome; 2) Job Involvement has a positive effect on Work Engagement; 3) Job Characteristics have a positive effect on Job Outcomes; 4) Job Involvement has a positive effect on Work Engagement; 5) Work Engagement has a positive effect on Job Outcome; 6) Job Involvement has a positive influence on Job Outcomes through Work Engagement as a mediating variable; and 7) Job Characteristics have a positive influence on Job Outcomes through Work Engagement as a mediating variable.Bahasa Indonesia Abstrak: Tujuan dari penelitian ini untuk mengetahui pengaruh 1) Job Involvement terhadap Job Outcome, 2) Job Involvement terhadap Work Engagement, 3) Job Characteristics terhadap Job Outcome, 4) Job Characteristics terhadap Work Engagement, 5) Work Engagement terhadap Job Outcome, 6) Work Engagement sebagai variabel mediasi antara Job Involvement terhadap Job Outcome, 7) Work Engagement sebagai variabel mediasi antara Job Characteristics terhadap Job Outcome. Responden dari penelitian ini adalah karyawan yang bekerja di PT XYZ. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif, dengan menggunakan pengumpulan data berupa kuesioner secara online. Teknik pengambilan data dalam penelitian ini menggunakan teknik nonprobability sampling dengan metode convenience sampling, dimana responden hanyalah karyawan yang bekerja di PT XYZ. Jumlah sampel yang digunakan dalam penelitian ini adalah 200 responden. Analisis data statistik dalam penelitian ini adalah menggunakan Structural Equation Modelling dimana pegolahan data menggunakan aplikasi SmartPLS 3.2.9 Hasil yang diperoleh dari penelitian ini adalah 1) Job Involvement berpengaruh positif terhadap Job Outcome, 2) Job Involvement berpengaruh positif terhadap Work Engagement, 3) Job Characteristics berpengaruh positif terhadap Job Outcome, 4) Job Involvement berpengaruh positif terhadap Work Engagement, 5) Work Engagement berpengaruh positif terhadap Job Outcome, 6) Job Involvement memiliki pengaruh positif terhadap Job Outcome melalui Work Engagement sebagai variabel mediasi, 7) Job Characteritics memiliki pengaruh positif terhadap Job Outcome melalui Work Engagement sebagai variabel mediasi.